CARDIOPROTECTIVE EFFECTS OF PHOSPHOCREATINE - V. V. Lomivorotov; M. N. Abubakirov; E. V. Fominskiy; V. A. Shmyrev (Вестник анестезиологии и реаниматологии, 2018)
Goal of the review: to review theoretical and practical aspects of using exogenous phosphocreatine in the patients with cardio-vascular disorders in various clinical situations, given that phospho-transporting system disorders are the one of pathogenic elements responsible for reduction of cardiac pumping ability.